Molecular simulation of a single-chain antibody against AChE to explore molecular basis of inhibitory effect of 3F3 McAb on enzyme activity. - Guo Chong-Zhi; Wu Jun-Hua; Wang Yu-Xia; Hu Yuan-Dong; Li Song; Sun Man-Ji (Acta Pharmacologica Sinica, 2016)
AIM: To explore the molecular basis of the inhibitory effect of 3F3, a monoclonal antibody against acetylcholinesterase (AChE), by computer-aided molecular simulation. METHODS: The single-chain 3F3 antibody (Sc3F3) was designed by joining VH and VL via a flexible linker (Gly4Ser)3. The amino acid sequence of the recombinant Sc3F3 was then subjected to computer-aided molecular modeling, and docking with the antigen molecule AChE to mimic the immunoactive interaction in a three-dimensional fashion. RESULTS: The modeled structure of Sc3F3 manifested the common features of a classical antibody. Both VH and VL were composed of two ?-sheets and connecting loops. The docking profile of the action between Sc3F3 with AChE demonstrated the formation of a stable structure. The van der Waals force played an important role suggesting that the complex was formed mainly via hydrophobic interactions between Sc3F3 and AChE molecules. CONCLUSION: The spatial structure of the complex of Sc3F3 and AChE showed that Sc3F3 overlaid the entrance of the active center gorge of AChE blocking the access of substrate.